Study of Subsonic Airfoil Based on the Assessment of Lift- To-Drag (L/D) Force Ratio - Hasalli Hj Ibrahim, Nur; Dzulhelmy bin Amari, Mohamad; Sharmila Shamsuddin, Zainon (International Journal of Engineering and Technology, 2019)
This paper focuses on the symmetrical model of NACA 0012 and performance of lift and drag forces to maintain the lift-to-drag (L/D) force ratio while cruising at air. The design modifications have been investigated to enhance the lift-to-drag force ratios for the subsonic airfoil. Initially, the study was conducted on the 2-D airfoil model of NACA 0012 and the results were compared experimentally and simulation using ANSYS 17.2 for all the conceptual designs. The analysis consideration for the airfoils design was indicated at 36 m/s constant velocity and zero angles of attack. The best possible conceptual design was developed which can perform at high lift forces, low drag forces and a high ratio of the lift-to-drag forces. It was found that the opportunity in the optimization of the subsonic airfoil based on the various effect of aerodynamic characteristics will be able to enhance the performance of subsonic airfoil.Â Â